Exploring the Teaching and Learning of Qualitative Analysis in Ghanaian Senior High Schools: Teaching and Learning of Qualitative Analysis - Nketsiah, John; Motlhabane, Abraham Tlhalefang (International Education Trend Issues, 2024)
This qualitative study investigates the instructional practices and learning outcomes of qualitative analysis in Ghanaian senior high schools. Data was collected through classroom observations, teacher and learner interviews. The schools' profiles and infrastructure revealed varying levels of resources, with School X having non-functional laboratory equipment, School Y lacking a functional science laboratory, and School Z boasting six well-equipped science laboratories. Non-participant classroom lesson observations were conducted to garner authentic insights into the teaching and learning of qualitative analysis. A total of 16 lessons were observed, followed by debriefing sessions with teachers to clarify instructional practices. The study aimed to explore the enacted chemistry curriculum in relation to the intended curriculum, shedding light on the challenges and opportunities faced by teachers and learners. The findings provide valuable implications for teacher education, professional development, and chemistry education policy in Ghana. By understanding the complexities of teaching and learning qualitative analysis, educators and policymakers can develop targeted interventions to improve student learning outcomes in science education.